A study of the activities and impact of the Asian Productivity Organisation (APO). Issue 2 (8th January 2019) - Adebanjo, Dotun; Mann, Robin; Mohammad, Musli; Bareduan, Salleh Ahmad
Abstract : Purpose: The purpose of this paper is to investigate the activities of the Asian Productivity Organisation (APO). The study identifies the various roles and activities of the APO and evaluates how well it performs in these roles. The study also investigates the impacts of the APO on the productivity initiatives of National Productivity Organisations (NPOs) in 16 Asian countries. These productivity initiatives are important in enhancing productivity performance and national competitiveness in the countries of interest. Design/methodology/approach: The study collects data from stakeholders in the NPOs in 16 countries. A Likert-scale questionnaire was used to collect data from two types of respondents – NPO CEOs and NPO professional/technical staff. Data were analysed by comparing the responses across the participating countries. Findings: The result shows that there was general satisfaction with the mission, vision and strategic direction of the APO. With respect to the operational performance of the organisation, the study showed that there were some differences in perception of the performance of the APO although the overall perception was positive. Practical implications: The study provides insights into the top management of the APO with regards to deciding on the future direction of the organisation and, in particular, the ways in which it understands and supports the varied requirements of the different NPOs. Originality/value: Organisations such as the APO dedicate significant resources into supporting NPOs, and by extension productivity-related commercial operations, in several countries. It is important to understand how these services are perceived and experienced in these countries, and a definitive study to examine this has not previously been carried out.